Melihat Faktor-Faktor Yang Mempengaruhi Minat Mahasiswa Dalam Berinvestasi Di Pasar Modal Untuk Pengembangan Galeri Investasi (Studi di Universitas Merdeka Madiun) - Saraswati Budi Utami; Siti Wardani Bakri Katti; Yogik Eko Prasetyo (Universitas Merdeka Madiun, 2020)
Abstractâ€” This study aims to determine the considerations taken by students of the Faculty of Economics, University of Merdeka Madiun to invest in the capital market through the Investment Gallery of Merdeka Madiun University. Some of the factors chosen to see the consideration in investing are (1) Minimum Capital variable, (2) Return variable, and (3) Capital Market Education variable. Students as investors still have limitations, so the factors that are considered in making investment decisions or investment interests are not too many. This research is an associative study because it is to determine the relationship between Minimum Capital for Investment, Return and Capital Market Education on Student Interest. The research analysis technique uses multiple linear analysis. Respondents in this study were still limited to the Faculty of Economics because in the Investment Gallery of Merdeka Madiun University most of the investors were from the Faculty of Economics. Meanwhile, from other faculties, knowledge of investment options is still common. This study used a sample of 106 students who met the criteria set, from a population of 417 students who had open accounts at the Investment Gallery of the Merdeka University of Madiun. The results showed that: (1) the Minimum Investment Capital variable partially had no significant effect on the Investment Interest variable, (2) the Return variable partially had a significant effect on the Investment Interest variable, (3) the Capital Market Education variable partially had a significant effect on the Interest variable. Investment, and (4) the Minimum Investment Capital, Return, and Capital Market Education variables simultaneously (simultaneously) have an effect on the Investment Interest variable. Of the three variables the dominant influence on student interest is Return. From the results of this research, it can be used as a basis for managers of the Investment Gallery at Merdeka Madiun University to develop a development strategy. Investors from students within the University of Merdeka Madiun itself can be increased through capital market education activities carried out on campus personally or by opening classes. In order to attract potential investors outside the campus, more intense education is also needed, through communities because investment in the capital market is still something new in Indonesian society.Â Keywordsâ€”: Investment Interests; Capital Market; Minimum Investment Capital; Return; Capital Market Education.